Perception and attitude of the general population toward Alzheimer’s disease in eastern region, Saudi Arabia - Hassan Alradi; Hassan Mohammed Alturaiki; Mohammed Ameen Alali; Nora Almuslim (Journal of Family Medicine and Primary Care)
Objectives: To measure the awareness of AD among the general population of Eastern Province, Saudi Arabia. Methods: A cross-sectional study was conducted in the Eastern Province of Saudi Arabia from October to November 2023. The data was collected using an online questionnaire. Results: A total of 614 eligible participants completed the study questionnaire. Among those surveyed, 99.3% had heard about Alzheimer’s disease (AD), while 96.1% associated it with memory loss. Additionally, 91.5% recognized that individuals with AD face risks when driving, 91.5% believed they could not independently handle their financial matters, 85.7% thought they could not make health-related decisions on their own, and 85.5% believed they could still participate in sports. Conclusion: The research results challenge our initial hypothesis by revealing significant AD awareness in Eastern Province, Saudi Arabia, largely attributed to internet-based health information. Despite this, there is a need to improve public attitudes toward Alzheimer’s patients, highlighting the importance of enhanced education and better communication between healthcare professionals and the public.